Appropriate Site Development in the Application of the Green Building Concept: An Evaluation of the Planning of Gianyar Public Market - Ni Ketut Agusintadewi; Ni Luh Eka Janiawati; Widiastuti Widiastuti (ARSITEKTURA, 2021)
Appropriate Site Development is one of the Greenship criteria for maintaining or expanding urban greenery in order to improve microclimate quality, decrease CO2 and other pollutants, avoid soil erosion, reduce drainage system loads, and keep the balance between clean water and groundwater systems. The GREENSHIP concept is a solution to the decline of the green spaces of Gianyar regency, which has been due to the construction of hotels and villas for tourism. The Government of Gianyar Regency in Bali Province is committed to applying the concept by planning Gianyar Public Market as the first public facility that uses the idea. This study evaluated whether the application of the Green Building concept, particularly the one in the category of Appropriate Site Development, will be beneficial for the users and the surrounding environment. The evaluation used mixed-methods, which incorporated a case study approach. Two key persons were interviewed. The collected interview data combined with the secondary data were processed with the GREENSHIP rating tools. Results of the evaluation show that, in the category of Appropriate Site Development, the planning of Gianyar Public Market obtains 41.18% points. It means that the planning has not yet adequately fulfilled the criteria. Therefore, some efforts and improvements need to be taken and made to fulfill the criteria of the categories in which the planning has not yet obtained maximum points. One of such categories is technology application.